Strengthening Teacher Creativity Models through Empirical Studies in High Schools - Desianti, Lisa; Hardhienata, Soewarto; Setyaningsih, Sri (Journal of Industrial Engineering & Management Research, 2022)
This study explores the creativity of teachers in schools. What are the things that affect the creativity of teachers in teaching in schools, both from the teacher's internal environment and the external environment? Teacher creativity is needed to motivate students to be more enthusiastic in learning so as to improve learning achievement. On the other hand, boring, teacher-oriented learning methods are no longer appropriate today. This study aims to build a model of teacher creativity by empirically examining what variables are thought to have an effect on strengthening teacher creativity. This research was conducted using a qualitative method through the process of interviewing and observing the principal of a private high school in the city of Bogor, West Java, Indonesia. Qualitative methods are carried out to obtain novelty in building models at the research locus. From the results of qualitative research the model of teacher creativity obtained.